Vertebroplasty and kyphoplasty: inefficient treatments for degenerative spine disease - Kasperk, Christian; Meeder, Peter-Jürgen; Nöldge, Gerd; Wiedenhöfer, Bernd; Ewerbeck, R.; Bardenheuer, Hubert J.; Grafe, Ingo Alexander; Huber, Franz-Xaver; Nawroth, Peter Paul (Experimental and clinical endocrinology & diabetes, 2010)
This review summarises the most recent clinical evidence from controlled studies on the outcome after osteoplastic procedures in painful osteoporotic vertebral fractures. On this basis implications for clinical and academic medicine are proposed.
Gesehen am 07.03.2023